The Clareon Vs AcrySof PanOptix Trifocal IOL: A Comparative Study of Patient Satisfaction and Visual Performance - Hovanesian JA; Jones M; Allen Q (Clinical Ophthalmology)
John A Hovanesian,1 Michael Jones,2 Quentin Allen3 1Harvard Eye Associates, Laguna Hills, CA, USA; 2Quantum Vision Centers, Swansea, IL, USA; 3Florida Vision Institute, Stuart, FL, USACorrespondence: John A Hovanesian, Harvard Eye Associates, 23961 Calle De La Magdalena, #300, Laguna Hills, CA, 92653, USA, Tel +1 949 951 2020, Fax +1 949 951 9244, Email jhovanesian@harvardeye.comPurpose: To evaluate patient-reported outcomes of cataract surgery using the Clareon Panoptix and Panoptix Toric trifocal lenses and to compare these to the data collected previously for the AcrySof Panoptix and Panoptix Toric.Patients and Methods: Prospective, open-label, multicenter analysis of satisfaction, spectacle independence, presence of unwanted side effects, and best-corrected visual acuity among patients undergoing cataract surgery who had been implanted at least 1 month previously with the Clareon PanOptix or PanOptix Toric trifocal IOL bilaterally. Results were compared to outcomes measured two years ago from a similar study with the AcrySof version of the same lens.Results: No significant differences in patient satisfaction rates were reported between the two cohorts. Spectacle independence was similar with 88% of Clareon Panoptix and 83% of AcrySof Panoptix patients having no need for any corrective lenses. Quality of vision was not statistically different with 7% of Clareon vs 15% of AcrySof patients reporting “very much” or more of glare/halo severity. Significantly more AcrySof (66%) than Clareon (42%) patients achieved a spherical equivalent outcome within 0.25 D of target. Best corrected distance visual acuity differences were not statistically significant, and no safety concerns were reported.Conclusion: The Clareon PanOptix trifocal lens provides similar satisfaction and spectacle independence and has a similar side effect profile and BCVA outcome to the identical lens made of the predecessor AcrySof lens.Plain Language Summary: In this prospective, non-interventional, open-label, multicenter analysis evaluating patient-reported outcomes 1 month after scheduled cataract surgery, patients had similar satisfaction and spectacle independence with the Clareon PanOptix and PanOptix Toric trifocal lenses when results were compared to a previous study of the same lenses made of the predecessor AcrySof lens.Keywords: cataract surgery, spectacle independence, glare, multifocal intraocular lens, lens material